Data on multiple body parameters, microclimatic variables, and subjective assessment of thermal sensation monitored in outdoor environment - Pantavou, Katerina (Data Brief, 2017)
This paper describes two sets of data on multiple body parameters of five participants, on microclimatic variables, and on self-reported assessment of thermal responses, all monitored in the same outdoor urban environment. Data were collected during three seasons, summer, autumn and winter 2010–2011, in the city of Athens, Greece. Part of these data, collected during the summer period, is related to the research article entitled "Case study of skin temperature and thermal perception in a hot outdoor environment." (Pantavou et al., 2014) [1].